Judicial accounting expertise: Foundations, applications, and challenges - Assma, Boudounet; Amira, Bahri (The International tax journal, 2025)
This research paper aims to explore forensic accounting expertise by examining various concepts related to expertise and forensic experts. The study employs a descriptive approach to analyze the legal framework, the challenges faced by forensic accounting expertise, and prospects for its development. The research yielded several key findings, including the following: forensic experts must possess both academic and practical qualifications to practice their profession; the judiciary relies on expert reports to issue rulings in cases brought before it; forensic accounting experts are indispensable, as judges often lack the technical knowledge required to resolve financial disputes; and forensic accounting expertise plays a crucial role in detecting fraud and tax evasion.